Rural and Small Town School Counselors - Richard E. Pearson; John M. Sutton Jr. (Journal of Research in Rural Education, 1999)
This study was designed to examine the role and practice ofschool counselors working in small town and rural school settings. Counselors were able to give voice to their experiences and views, focusing on such issues as organizational smallness, role generalization, and professional autonomy. Implications for practice and further research were addressed through a series ofquestions relating to counselor role, function, and inservice training